Midpregnancy testing for soluble fms-like tyrosine kinase 1 (sFlt-1) and placental growth factor (PlGF): An inter-assay comparison of three automated immunoassay platforms. (October 2019) - Black, Carin; Al-Amin, Ahmed; Rolnik, Daniel Lorber; Kane, Stefan C.; Stolarek, Caroline; White, Adrienne; da Silva Costa, Fabricio; Brennecke, Shaun
Abstract: We performed an inter-assay comparison among three immunoassay platforms for midpregnancy testing of sFlt-1, PlGF and the sFlt-1/PlGF ratio, which are established markers for pre-eclampsia. Maternal blood was collected 19–22 weeks' gestation. Raw data values were converted to multiples of the median (MoM). PlGF and sFlt-1 values among platforms were highly correlated (p < 0.001). There was significant variation in raw data values for PlGF and sFlt-1 among platforms, eliminated following conversion to MoM. When directly comparing raw data values among platforms, platform-specific reference ranges values should be used. MoM values were equivalent among platforms, allowing direct inter-assay result comparison. Highlights: There was significant variation in raw data values for both PlGF and sFlt-1 among the three platforms. Raw data values require platform-specific reference ranges for inter-assay comparison of results. This variation was essentially eliminated by converting raw data values to MoM. MoM values were equivalent among platforms, allowing direct inter-assay result comparison.